Accelerated learning programme for robotic competition - Othman, Azam; Shafie, Amir Akramin; Zainal Abidin, Zulkifli; Mohd Mustafah, Yasir; Pawanchee, Shahril; Amir, Nur Syamimi; Shabu, Shahrul Fhaizal; Abdul Aziz, Mazlan (Knowledge Transfer Programme © Knowledge Transfer Centre, 2017)
Robotic education and industrial collaboration are among effective strategies to facilitate students learning of Science, Technology, Engineering and Mathematics (STEM) and a possible future career in engineering. One of the strategic initiatives of Ministry of Higher Education (MOHE) is to enhance partnership and collaboration with private companies through Knowledge Transfer Programmes (KTP). This paper presents a case study of knowledge transfer in industrial collaboration between Kulliyyah of Engineering, International Islamic University Malaysia (IIUM) and WNF Resources Sdn. Bhd. The main purpose of this KTP project was to transfer knowledge and skills on robotics learning to WNF through accelerated learning programmes provided by experts from Kulliyyah of Engineering. The main activities of this project included initiating robotic supplier, conducting robotics workshops, establishing a business unit for educational robotics training, and transferring robotics design knowledge and skills to graduate interns. Overall, the KTP programme was very useful in enhancing the capacity of WNF’s core business. For this programme, IIUM contributions in terms of the technical development of robotics learning system, namely, the Mimibot and the industrial partner manage to sell 29 units of the kits. This KTP programme also helps the company to improve its branding and marketing of the Mimibot to schools. This programme managed to train students from 3 different schools in Malaysia as well as students from 1 Indonesian school. One of the programme’s significant achievement was to enable the Malaysian students from the 3 schools to improve their performance and win robotic competitions. Besides improving students’ performance, this programme helps to set up new robotics clubs in selected schools. In conclusion, this KTP programme manages to assist WNF in becoming an educational and engineering training partner for schools that are interested to offer robotics learning to their students.